ANALYSIS OF THE INFLUENCE OF FINANCING ON THE VALUE OF SHARIA BANKS WITH PROFITABILITY AS INTERVENING VARIABLES - Azizuddin, Imam (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
This study aims to analyze the influence of NUC and NCC financing on Sharia commercial banks' value using variable profitability as variable intervening. The data used in exploring the impact of this financing is obtained from the financial statements issued by OJK with data from 2016-2019. The data analysis used in this study uses path analysis. This study shows that nuc has a significant effect on profitability but has no significant impact on the value of sharia banks. In contrast to the NCC results that have absolutely no significant impact on Sharia banks' profitability and value. This study also provides information that nuc has no effect on the importance of sharia banks with profitability as variable intervening, in contrast to NCC, which affects the value of sharia banks with profitability as variable intervening.